2020
DOI: 10.7554/elife.50631
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic signature in nucleus accumbens for anti-depressant-like effects of acetyl-L-carnitine

Abstract: Emerging evidence suggests that hierarchical status provides vulnerability to develop stress-induced depression. Energy metabolic changes in the nucleus accumbens (NAc) were recently related to hierarchical status and vulnerability to develop depression-like behavior. Acetyl-L-carnitine (LAC), a mitochondria-boosting supplement, has shown promising antidepressant-like effects opening therapeutic opportunities for restoring energy balance in depressed patients. We investigated the metabolic impact in the NAc of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 93 publications
6
48
0
Order By: Relevance
“…L-Carnitine has demonstrated some beneficial effects on axonal development and branching in sensory neurons (Sainath et al, 2017). Furthermore L-Carnitine has anti-depressant effect mediated by an upregulation of metabolic activity (Cherix et al, 2020;Filiou and Sandi, 2019). Our work provides further evidence that L-Carnitine might be of therapeutic interest in correcting mitochondrial disfunction and metabolic imbalance during neurodevelopment.…”
Section: Discussionsupporting
confidence: 52%
“…L-Carnitine has demonstrated some beneficial effects on axonal development and branching in sensory neurons (Sainath et al, 2017). Furthermore L-Carnitine has anti-depressant effect mediated by an upregulation of metabolic activity (Cherix et al, 2020;Filiou and Sandi, 2019). Our work provides further evidence that L-Carnitine might be of therapeutic interest in correcting mitochondrial disfunction and metabolic imbalance during neurodevelopment.…”
Section: Discussionsupporting
confidence: 52%
“…A possible reason for this discrepancy may be the different stress protocols used (i.e., 10-days chronic social defeat 18 vs. the here applied 3-week mCRS). Note, however, that a 3-way chronic restraint protocol results as well in major metabolic changes in the NAc in stress-vulnerable mice 54 . In the future, it will be important to integrate transcriptomic and metabolic analyses in these two brain regions, ideally at the cell-type level, to further our understanding of stress-induced metabolic regulation at the transcriptional level.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the GR implicated in the mesocorticolimbic dopamine system with chronic stress vulnerability 85 , 86 , and showed that the GR has the capability to translocate into brain mitochondria 68 , 87 , 88 and to bind on the mitochondrial genome 56 , 89 in a glucocorticoid-dependent manner 56 . It will also be important to test whether mitochondrial-targeted interventions known to ameliorate stress and anxiety responses 54 , 90 92 would reverse both the behavioral and mtDNA transcriptional changes observed in stress-vulnerable mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the power to detect a significant behavior-metabolite association in the occipital lobe was lower, and it would be important in future studies to verify the specificity of the reported associations for the NAc. In this study, only males were included as our prediction for a link between accumbal metabolism and motivated performance was inspired in background studies involving male rodents [59,72,73]. In addition, due to technical challenges mainly associated with scanning at 7 T, our original participant recruitment was reduced to a moderate sample size, which limits the generalization of the obtained results.…”
Section: Discussionmentioning
confidence: 99%